PROSEDUR AUDIT AKUN PENDAPATAN PADA PERUSAHAAN JASA KONSULTAN OLEH KAP SSS - Annisa Azzahra, (2022)
Before the company's financial statements are issued, an audit must be carried out by an auditor to reduce the presence of fraud in the financial statements. In this report, the audit procedures of revenue accounts carried out by KAP SSS for its client, one of the consulting service companies will be discussed in detail. Revenue is a cash inflow caused by the company's operational activities. In recognizing and recording the company's income, it must be based on PSAK 72, which is currently generally accepted for revenue accounts. The audit procedure of revenue accounts is a method the auditor uses to obtain complete audit evidence to assess whether the recording and recognition of the company's revenue accounts are appropriate and follow applicable standards. Based on the analysis of the five steps model in PSAK 72 and audit procedures on revenue accounts carried out, PT ACR has recognized and recorded revenue following applicable accounting standards, and revenue accounts at PT ACR have been presented fairly without any material misstatements.